2021
DOI: 10.3390/e23060656
|View full text |Cite
|
Sign up to set email alerts
|

Regional Population Forecast and Analysis Based on Machine Learning Strategy

Abstract: Regional population forecast and analysis is of essence to urban and regional planning, and a well-designed plan can effectively construct a sound national infrastructure and stabilize positive population growth. Traditionally, either urban or regional planning relies on the opinions of demographers in terms of how the population of a city or a region will grow. Multi-regional population forecast is currently possible, carried out mainly on the basis of the Interregional Cohort-Component model. While this mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Whereas previous studies have employed RFs to model gentrification (Reades et al, 2019;Palafox & Monasterio, 2020), these results demonstrate the ability of boosting methods to further improve the accuracy of predictive neighbourhood change models. These findings may have applicability to other fields of urban studies using ML modelling, such population forecasting, property price prediction, and demographic modelling (e.g., Wang & Lee, 2021;Cesare et al, 2017).…”
Section: Model Comparisonmentioning
confidence: 76%
See 1 more Smart Citation
“…Whereas previous studies have employed RFs to model gentrification (Reades et al, 2019;Palafox & Monasterio, 2020), these results demonstrate the ability of boosting methods to further improve the accuracy of predictive neighbourhood change models. These findings may have applicability to other fields of urban studies using ML modelling, such population forecasting, property price prediction, and demographic modelling (e.g., Wang & Lee, 2021;Cesare et al, 2017).…”
Section: Model Comparisonmentioning
confidence: 76%
“…Firstly, the paper employs more powerful tree-based models than previous ML gentrification studies (Reades et al, 2019;Palafox & Monasterio, 2020). The improved performance of boosting methods over random forests enables more accurate and effective neighbourhood change predictions, while also having application in wider urban land use change problems (e.g., Wang & Lee, 2021). Furthermore, the study incorporates a novel model explanation tool that delineates the influence of each variable on the model output for specific model predictions.…”
Section: Gentrification and The Importance Of Quantificationmentioning
confidence: 99%
“…In [20] has been applied three machine learning methods such as Linear Regression model, LSTM model, and XGBoost Regression model for analyzing and forecasting the population growth of large cities in Taiwan. The prediction result of each model is compared based on MAPE.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rappaport 20 and Rodríguez‐Pose and Ketterer 21 highlight that improved infrastructure conditions facilitate attracting more people to relocate. Additionally, Wei et al 10 and Wang and Lee 22 respectively identified urbanization rate and local public expenditure as crucial factors influencing population dynamics. Secondly, the economic level provides a comprehensive reflection of factors such as GDP, income, and employment, which serve as the primary internal drivers of population growth 23 , 24 .…”
Section: Literature Reviewmentioning
confidence: 99%